Productive Zakat Model for Micro-Entrepreneur Development - Efri Syamsul, Bahri; Mohd Mizan, Mohammad Aslam; Hendro, Wibowo (2019)
There are 56.4 million micro and small businesses (MSEs) in Indonesia, as many as 30% have accessed financing. Meanwhile, as many as 70% do not have access to bank financing. It is because micro-entrepreneurs have no guarantees, and there is a perception of a high-risk profile. As a result, micro-entrepreneurs' conditions have not changed, they are still in poor condition, and their businesses are underdeveloped. Productive Zakat becomes a solution for the development of micro-entrepreneurs. This study describes how the micro-entrepreneurship development model is implemented by the National Board Zakat (BAZNAS). This research is a qualitative method and using a descriptive approach and a literature study. The results showed that the BAZNAS micro-entrepreneurship development model was carried out through the BAZNAS Institute of Mustahiq Economic Empowerment (LPEM) with programs namely: Mustahiq entrepreneurs and Z-Mart. Productive Zakat is distributed to micro-entrepreneurs in capital, training, assistance, and product development. Productive Zakat for microentrepreneurs' development can increase the income of micro-entrepreneurs by 48.49% from IDR 4,404,911.00 before receiving zakat funds to IDR 6,540,746.00.